2001
DOI: 10.1152/ajpheart.2001.280.1.h189
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 MAP kinase in endothelial cell alignment induced by fluid shear stress

Abstract: The p38/mitogen-activated protein (MAP) kinase-activated protein kinase 2 (MAPKAP kinase 2)/heat shock protein (HSP)25/27 pathway is thought to play a critical role in actin dynamics. In the present study, we examined whether p38 was involved in the morphological changes seen in endothelial cells (EC) exposed to shear stress. Cultured bovine aortic EC were subjected to 14 dyn/cm(2) laminar steady shear stress. Peak activation of p38, MAPKAP kinase 2, and HSP25 were sixfold at 5 min, sixfold at 5 min, and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 50 publications
7
107
1
Order By: Relevance
“…Modulation of the activities of the Rho, Rac, and cdc42 GTPase activities, which are primary regulators of actin assembly, 37 have been implicated in these morphological responses; 29 furthermore, inhibition of shear activation of p38 MAP kinase blocked downstream activation of the actin uncapping protein, HSP27, and abolished cell shape change. 38 Usually cell shape change produced by actin assembly is secondary to formation of filopodia or lamellipodia; however, this was not the case for shear-stressed endothelium. Instead, assembly was concentrated at the ends of stress fibers that were randomly oriented.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of the activities of the Rho, Rac, and cdc42 GTPase activities, which are primary regulators of actin assembly, 37 have been implicated in these morphological responses; 29 furthermore, inhibition of shear activation of p38 MAP kinase blocked downstream activation of the actin uncapping protein, HSP27, and abolished cell shape change. 38 Usually cell shape change produced by actin assembly is secondary to formation of filopodia or lamellipodia; however, this was not the case for shear-stressed endothelium. Instead, assembly was concentrated at the ends of stress fibers that were randomly oriented.…”
Section: Discussionmentioning
confidence: 99%
“…We and other laboratories have reported that fluid shear stress activates several members of the MAPK family including extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), and p38 MAPK in cultured bovine ECs (1,25). In addition, another distinct but important cell signaling pathway, phosphatidylinositol 3-kinase-AKT, has been shown to be activated by fluid shear stress and other hemodynamic forces (26,27).…”
Section: Vascular Endothelial Cells (Ecs)mentioning
confidence: 99%
“…Activation of the MAPKs and AKT was assessed by determining phosphorylation of ERK1/2, p38 MAPK, and AKT with immunoblotting using phosphospecific antibodies (Cell Signaling) as described previously (25,26,35). In brief, after exposure to the shear stress, ECs were lysed in 50 mM HEPES, 150 mM NaCl, 10% glycerol, 1 mM EDTA, 100 mM NaF, 10 mM sodium pyrophosphate, 1% Triton X-100, 1.5 mM MgCl 2 , 1 mM Na 3 VO 4 , 10 g/ml leupeptin, and 1 mM phenylmethylsulfonyl fluoride.…”
Section: Immunoblottingmentioning
confidence: 99%
“…For endothelial cells, p38 MAPK is elevated during incubation at high glucose concentrations, and p38 MAPK inhibition prevents cytoskeletal rearrangement in response to shear stress. 11,12 However, any potential consequences for endothelial vasodilator function in diabetes have not been determined. Thus, the aim was to assess the effects of the p38 MAPK inhibitor, LY2161793, on neurovascular function in corpus cavernosum from diabetic mice.…”
Section: Introductionmentioning
confidence: 99%